2023
DOI: 10.31729/jnma.8118
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic Retinopathy among Patients with Prediabetes Attending the Outpatient Department of Ophthalmology in a Tertiary Eye Care Centre: A Descriptive Cross-sectional Study

Abstract: Introduction: Diabetic retinopathy is a specific microvascular ocular complication associated with diabetes. However, retinopathy has also been reported in people with prediabetes. The study aimed to find out the prevalence of diabetic retinopathy among patients with prediabetes attending the outpatient Department of Ophthalmology in a tertiary eye care centre. Methods: A descriptive cross-sectional study was conducted among patients with prediabetes attending the outpatient Department of Ophthalmology in a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Obesity is a significant social problem. It predisposes to the development of carbohydrate metabolism, hypertension, and ischemic stroke, which may increase the risk of developing retinopathy in people during prediabetes as well as those diagnosed with diabetes [ 133 , 134 , 135 ]. However, the findings from various studies investigating the relationship between obesity and DR have been inconclusive.…”
Section: The Role Of MD In the Treatment And Prevention Of Obesity An...mentioning
confidence: 99%
“…Obesity is a significant social problem. It predisposes to the development of carbohydrate metabolism, hypertension, and ischemic stroke, which may increase the risk of developing retinopathy in people during prediabetes as well as those diagnosed with diabetes [ 133 , 134 , 135 ]. However, the findings from various studies investigating the relationship between obesity and DR have been inconclusive.…”
Section: The Role Of MD In the Treatment And Prevention Of Obesity An...mentioning
confidence: 99%
“…Several studies have reported associations between microalbuminuria and DR in prediabetics [57,72]. The association of retinopathy with dyslipidemia is varied, and there are reports published on the associations of hypercholesterolemia and retinal lesions (hard exudates) and also between hypertriglyceridemia-and diabetes-induced retinopathy [33,58,73,74].…”
Section: Comorbid Ocular and Metabolic Diseasementioning
confidence: 99%